2(v-7)-4v=4

Simple and best practice solution for 2(v-7)-4v=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v-7)-4v=4 equation:


Simplifying
2(v + -7) + -4v = 4

Reorder the terms:
2(-7 + v) + -4v = 4
(-7 * 2 + v * 2) + -4v = 4
(-14 + 2v) + -4v = 4

Combine like terms: 2v + -4v = -2v
-14 + -2v = 4

Solving
-14 + -2v = 4

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -2v = 4 + 14

Combine like terms: -14 + 14 = 0
0 + -2v = 4 + 14
-2v = 4 + 14

Combine like terms: 4 + 14 = 18
-2v = 18

Divide each side by '-2'.
v = -9

Simplifying
v = -9

See similar equations:

| 24x^3-14x^2-x+1=0 | | 35/8= | | 6u^2+13u+5=0 | | 2=-3x+8 | | 49=9y-68 | | 6xy=3x^2 | | y=-3(3)+8 | | 6x+42=2x-2 | | 2y-3+5y=y+15 | | 3x+6y=45 | | 2,295=-74t | | 7y+8(y+6)= | | 3*x+6=5*x | | 8c-4=2-4c | | (x+2)(2x+1)=(x+6)(2x+3) | | 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 | | 8+13=-3(7x-7) |

Equations solver categories